PENGARUH KINERJA MODAL INTELEKTUAL, PERTUMBUHAN PENJUALAN, DAN FAKTOR LAINNYA TERHADAP FINANCIAL DISTRESS - Gunawan, Patricia; Mulyana, Ricky A. (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted to obtain empirical evidence and also analyze factors that can influence the dependent variabel is financial distress. The independent variabels used in this research are current ratio, cash ratio, debt to total asset ratio, sales growth, institutional ownership and intellectual capital.The population used in this research are consumer cyclicals, consumer non-cyclicals and transportation and logistic listed on the Indonesia Stock Exchange during the 2019-2022 period. The sample in this research consists of 182 companies or 546 data obtained through purposive sampling method. To test the hypothesis, this research used logistic regression. The results of this research show that intellectual capital performance affect financial distress. Meanwhile, current ratio, cash ratio, debt to total asset ratio, sales growth,and institutional ownership do not affect financial distress.